Germany's Conscience: Friedrich Meinecke: Champion of German Historicism - Krol, Reinbert (Zeit, Sinn, Kultur., 2021)
Questions of truth, ethics, state power, and propaganda, of how to render account of catastrophes and reconcile oneself with one's past are not only crucial to our time, they were also central to the German historian Friedrich Meinecke (1862-1954). Probably no generation of historians before Meinecke had lived through more unsettling transformations, during which these questions were most pressing. Reinbert Krol's analysis of Meinecke's intellectual development does not only give us insight into his philosophy of history - which turns out to be more conciliatory than previously assumed - it can also be a source of inspiration for scholars of history today.